TECHNOLOGICAL SOLUTIONS FOR COLLABORATIVE WORK WITHIN THE LIFELONG LEARNING - Manako, A.; Voychenko, O. (Journal of Information Technologies in Education (ITE), 2014)
Recent years demonstrate significant transformations in the field of education. The reply to the challenges of globalization and modern information society is implementation of lifelong learning paradigm (LL). The implementation of LL paradigm suggests a more complex and flexible learning process than the traditional one, with essential role of collaborative work of virtual teams. Maximum efficiency of virtual teams is achieved through the flexible use of the combination of both basic functional components and auxiliary tools based on cloud services. This task can be solved by creating a modern ICT-based environment, which implements an effective information support to collaborative work of the members of virtual teams. The environment provides technological solutions for the virtual teams and communities. It also provides features to implement flexible roles distribution, depending on the specifics of the addressed problem and the level of involvement of a particular user in the learning within the LL paradigm.